Alterações fisiológicas e de produção do Caupi (Vigna unguiculata (L.) Walp) cultivado em Solo Aluvial Sódico e irrigado com diferentes lâminas de água - Porto Filho, Francisco de Queiroz (1986)
An experiment was carried out at the "Fazenda Experimental do Vale do Curu", Pentecoste County, State of Cearã, Brazil, in a soil of the Vertic Torrifluven type, to evaluate changes in physiological, and yield parameters on cowpea (Vigna unguiculata (L.) Walp.) EPACE-1 cultivar irrigated at different depths of water [...]